EVALUASI KEPUASAN PENGGUNASISTEM INFORMASI AKADEMIK PERGURUAN TINGGI MENGGUNAKAN STANDAR ISO 9126 - Rahayu Amalia; Alek Wijaya (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2018)
Universitas Bina Darma has implemented an academic system located at http://sisfo.binadarma.ac.id. In the academic system, there is some information that can be obtained by the students. From all menus contained in Universitas Bina Darma academic system it can be seen that all the prepared information is indeed very important and helpful especially for college students. With regard to the importance and the benefits felt by students it will arise a perceived satisfaction of information obtained from the academic system. To measure the level of satisfaction of students against the University's academic system Bina Darma then used standard ISO 9126. The results showed that the six components of the standard ISO 9126 provide enough our satisfaction for the students in the use of academic information systems.